Validating the DDTK Instrument for Analyzing Children's Brain Development on the Neurotune Android Application - evi mulyati; Erna Budiarti; Anne Gracia; Dewi Mahmuda; Retno Palupi; Dwi Adrian; Siti Rodiah (Universitas Panca Sakti Bekasi, 2023)
This paper aims to carry out construct validation of the Early Detection of Growth and Development (DDTK) questionnaire on the NeuroTune android application which is arranged according to the order of development of brain function. The DDTK questionnaire from the international screening instrument is the Denver Developmental Screening Test II (DDST) which does not provide profile information on learning readiness, other than language development, personal social, fine motor, gross motor. The components of the Denver II Test instrument were then translated and developed into part of the Early Detection of Growth and Development by grouping:KPSP (Developmental Pre Screening Questionnaire)TDD (Hearing Test)TDL (Visibility Test)In line with the emergence of the development of brain function maturity, the instruction sentences on the DDTK instrument are then sequenced referring to the emergence of brain function which provides a profile of brain function maturity for learning readiness. The qualitative validation method for the standard instruments arranged in this sequence uses the Lawshe CVI (Content Validity Index) and CVR (Content Validity Ratios) methods, content validation refers to a process that aims to determine whether an instrument (checklist, questionnaire, or scale) is at expected content area to measure. The validators consist of experts in the fields of Early Childhood Education, Neurology, and Statistics. The results of the validation are expected to be a reference for using questionnaires in the education community and parents of children aged 4-8 years to help find a profile of the need for learning readiness assistance that displays information on stimulus needs for brain function maturity.